2018
DOI: 10.2147/idr.s174140
|View full text |Cite
|
Sign up to set email alerts
|

The rs1625579 T&gt;G polymorphism in the <em>miRNA-137</em> gene confers a risk of early-onset Kawasaki disease in a southern Chinese population

Abstract: BackgroundKawasaki disease (KD) mainly manifests as excessive inflammation and vascular endothelial cell injury. This disease generally occurs in children younger than 5 years of age and is more severe in children younger than 12 months. KD affects males and females at a ratio of 1.5:1. Polymorphisms of the rs1625579 locus in the miR-13 gene are associated with schizophrenia susceptibility, and high glucose-induced upregulation of miR-137 in vascular endothelial cells promotes monocyte chemotaxis and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…18 We found that miRNA-137 rs1625579 T>G is associated with the onset of Kawasaki disease in the same population in children younger than 1 year old. 16 To our knowledge, this report is the first on the association of miRNA-196a2 rs11614913 T>C with Kawasaki disease susceptibility among children in South China.…”
Section: Discussionsmentioning
confidence: 75%
See 1 more Smart Citation
“…18 We found that miRNA-137 rs1625579 T>G is associated with the onset of Kawasaki disease in the same population in children younger than 1 year old. 16 To our knowledge, this report is the first on the association of miRNA-196a2 rs11614913 T>C with Kawasaki disease susceptibility among children in South China.…”
Section: Discussionsmentioning
confidence: 75%
“…The control group was composed of 623 healthy Chinese children who went to the hospital for physical examination in the same period. [16][17][18] Peripheral venous blood was taken from each child to extract DNA.…”
Section: Study Subjectsmentioning
confidence: 99%
“…All participants recruited were unrelated Chinese Han individuals from southern China. A total of 623 healthy controls and 532 patients diagnosed with KD were recruited from January 2012 to January 2017 as we described previously . Two milliliters of fresh blood was collected from each participant, and 200 µL of each blood sample was employed to extract DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The groups mentioned above are based on American Heart Association (AHA) and can be concretely grouped according to coronary artery and age. (27, 28)SAS software (version 9.4; SAS Institute, Cary, NC) in motion carried out all Statistical analyses quickly.…”
Section: Methodsmentioning
confidence: 99%